Inovasi Kepemimpinan Kepala Madrasah Dalam Meningkatkan Prestasi Belajar Siswa di MA Tarbiyatul Ihsan Lemah Kembar Sumberasih Probolinggo - Anik Huzaimah; Endah Tri Wisudaningsih; Mohammad Ahyar Ma’arif (Departement of Mathematics Education, 2023)
The Education Office has developed several educational institutions by forming education which also teaches about religion. In order for the madrasah organization to be more productive, the leadership position of the madrasah head is very decisive. The madrasa head plays an important role in encouraging the growth and development of the institution. The purpose of the researchers to conduct research at the Weak Kembar Sumberasih Probolinggo Madrasah Aliyah is to find out whether the ideas put forward in the previous section are in accordance with the facts on the ground. Aliyah is a weak twin Sumberasih Probolinggo. This research uses a qualitative method, and the type of research is problem research. The procedures used in collecting information are monitoring (observation), selection (documentation), and question and answer (interviews). From the research we have carried out, the efforts of school principals to improve student learning achievement by providing motivation while providing special time for students by studying in the online learning library and giving homework using Android as a learning medium.